Teoría política posfundacional en La guerra del fin del mundo de Mario Vargas Llosa: ¿Canudos postestructuralista? - Martín Retamozo (Orbis Tertius, 2011)
It can be said that the relation between literature and political theory is not as prolific as that established by other disciplines such as philosophy, history and psychology. Although politics has held a central role in literature it is difficult to assert the prominence of political theory. A remarkable exception to this can be found in the novel La guerra del fin del mundo by Mario Vargas Llosa, not because the author dedicates himself to political theory but because of the complicity the plot shares with some contemporary theoretical perspectives. Within this horizon, the article proposes a reading of La guerra del fin del mundo in the light of its relation with key categories from post foundational political thought such as Heterogeneity, Antagonism, constitutive outside, empty signifier, discourse and hegemony. The article thus aims to contribute to the discussion of theoretical categories whose abstraction has often turned them difficult to assimilate. It also offers some reading clues to approach Vargas Llosa?s novel in the light of present political theory